State-mandated transparency: a discussion and examination of deadly force data among law enforcement agencies in Texas - Shjarback, John A. (Journal of crime and justice, 2019)
The current paper provides a critical assessment of the available data on police use of deadly force, including the lack of official, national-level measures, and the recent scholarly reliance on Internet, crowd sourced information. In addition, it presents an alternative data source on the topic in the form of legislative, state-mandated collection systems. Starting in September of 2015, Texas became one of a handful of states in which law enforcement agencies are now required to report all incidents where police gunfire injures and/or kills a citizen. This paper previews the Texas data - including its strengths and weaknesses - in addition to performing a descriptive analysis of police shootings that resulted in injury/death for years 2016 and 2017. The potential for state-mandated data collection programs to impact research, accountability, and policy are discussed.